Association of Circulating Tissue Inhibitor of Metalloproteinases‐1 and Procollagen Type III Aminoterminal Peptide Levels With Incident Heart Failure and Chronic Kidney Disease - Lieb, Wolfgang (J Am Heart Assoc, 2019)
BACKGROUND: Tissue inhibitor of metalloproteinases‐1 (TIMP‐1) and procollagen type III aminoterminal peptide are established circulating markers of extracellular matrix remodeling and associated with cardiovascular disease. The association of both biomarkers with incident congestive heart failure and chronic kidney disease (CKD) in the community is not well studied. METHODS AND RESULTS: We measured plasma total TIMP‐1 and procollagen type III aminoterminal peptide levels in 922 Framingham participants (mean age, 57 years; 57% women) and related both biomarkers to the risk of incident CKD and congestive heart failure in multivariable‐adjusted Cox regression models. Plasma total TIMP‐1 levels were positively associated with risk of incident CKD (164 events; hazard ratio per 1 SD in log‐biomarker, 1.90; 95% CI, 1.53–2.37) in multivariable models, including adjustments for left ventricular mass, C‐reactive protein, and B‐type natriuretic peptide levels. The association of total TIMP‐1 with risk of congestive heart failure was statistically significant in an age‐ and sex‐adjusted model, but was attenuated upon adjustment for conventional risk factors. Blood procollagen type III aminoterminal peptide levels were not related to the risk of CKD or congestive heart failure. CONCLUSIONS: Higher baseline levels of total TIMP‐1 conferred an increased risk for incident CKD, independent of conventional risk factors and circulating biomarkers of chronic systemic inflammation and neurohormonal activation. Our prospective observations in a large community‐based sample support the role of matrix remodeling in the pathogenesis of CKD.